(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Field experiments were conducted to quantify the effects of nicosulfuron on biological production of weedy sunflower (Helianthus annuus). Plants of this weed species were sown in plots sized 5x4.2 m with inter-row spacing of 24 cm, and 70 cm distance between rows. Plants with two pairs of developed leaves were treated with nicosulfuron using the next rates: 0, 10, 20, 40, 60 and 80 g a.i. ha-1. Vegetative parameters (plant height, fresh weight and leaf area) were recorded five times during vegetation, including the first measurement just before herbicide application and four measurements at intervals of about two weeks. Head and seed production (number of heads per plant, head weight, head diameter, weight of seeds per head, weight of seeds per plant, number of seeds per plant) were determined after seed maturity. The application of nicosulfuron caused growth reduction of weedy sunflower in comparison with the control. All application rates of this herbicide reduced vegetative (height, fresh weight, leaf area) and some generative (number of heads per plant, weight of seeds per plant, number of seeds per plant) parameters, which decreased with increasing rates of nicosulfuron. Effects on the remaining generative test parameters (head weight, head diameter, weight of seeds per head) were not analogous to the effects on other parameters.